(untitled) (Avocetta, 2025)
Lanner Falcon (Falco biarmicus feldeggii) is classified as endangered in Greece. Its breeding population is considered stable, with a patchy distribution on the mainland and the islands. Thessaly is considered one of the species’ strongholds due to its arid climate, connecting the subpopulations of western and northern Greece to those in the south. This is the first dedicated pilot survey for the species in Greece. Historical and citizen-science data were compiled, and the prefecture was divided into seven sectors. Favourable areas were classified based on the abundance of past and recent observations, as well as the species’ probability of presence. A total of 6,052 km was covered, with 107 field days and 480 monitoring hours invested from viewpoints during the breeding season. The species was recorded fifteen times, and eight territories were verified. Based on historical data, in four of the seven sectors, the species shows 59% decline. No fledglings or reproductive activity were recorded during 2024.